Predictors of Sleep Duration in Undergraduate Students Attending a Health Sciences University in Japan. - Eakman, Aaron M.; Kawakatsu, Yuki; Takahata, Miki; Kudo, Daisuke; Satake, Shinji; Sato, Toshiaki (Internet Journal of Allied Health Sciences & Practice, 2025)
Purpose: Inadequate sleep is a pressing public health concern contributing to absenteeism and poor school performance, especially in health sciences students. In this study we investigated the sleep quality and duration of undergraduate students in a prefectural university of health sciences program and explored factors explaining sleep duration (i.e., < 6 hours per night vs > 6 hours) using multiple variable logistic regression. Method: This cross-sectional survey study included 369 nursing, occupational therapy and physical therapy students who completed Japanese versions of the Pittsburg Sleep Quality Index, in addition to well validated sleep-related and mental health-related assessments. Results: We found just 11.7% of the sample reported low sleep quality, though 40.1% of the samples could be characterized as experiencing sleep debt. Within the logistic regression model 14.5% of sleep duration categorization could be explained. The model best explained factors promoting longer sleep duration (i.e.,> 6 hours), including shorter commuting times, fewer difficulties falling and staying asleep, lesser daytime sleepiness, more effective sleep hygiene practices, a "momingness" chronotype preference, and a less agreeable personality type. Conclusion: We discuss findings related to Buysse's model of sleep health and offer suggestions for the promotion of sleep health in health sciences university students.